Disease Severity and Molecular Identification of Banana bunchy top virus, Infecting Local Banana in Bali Island - Gusti Ngurah Alit Susanta Wirya; I Putu Sudiarta; Dewa Gede Wiryangga Selangga (Jurnal Perlindungan Tanaman Indonesia, 2020)
Bunchy top symptoms on banana has been reported in Bali Island since early 2011. Symptoms variation were observed in the field similar to infection of Banana bunchy top virus (BBTV). The identity of the BBTV in Bali on the basis of DNA-S nucleotide sequence has not been studied, therefore research was conducted to identify the species of BBTV infecting local banana in Bali based on sequence analysis. Research activities were initiated by collecting field samples from several local banana growing areas in Bali Island. Incidence of bunchy top disease in all locations reached 8% to 44% with disease severity ranged from 2.6% to 30%. Identification of BBTV from field samples were done by polymerase chain reaction using specific primers for BBTV (CPF/CPR) followed by sequence analysis of amplified DNA target. Specific BBTV DNA fragment was successfully amplified from 10 field samples; sequence analysis of DNA fragments showed their highest homology with BBTV. In addition the phylogenetic analysis confirmed the close relationship of  BBTV  isolates from Bali with various BBTV isolates from Indonesia and other isolates from the Asian group in GeneBank.